2008
DOI: 10.2140/agt.2008.8.1
|View full text |Cite
|
Sign up to set email alerts
|

Examples of exotic free 2–complexes and stably free nonfree modules for quaternion groups

Abstract: This is a continuation of our study [3] of a family of projective modules over Q 4n , the generalized quaternion (binary dihedral) group of order 4n. Our approach is constructive. Whenever n 7 is odd, this work provides examples of stably free nonfree modules of rank 1, which are then used to construct exotic algebraic 2-complexes relevant to Wall's D(2)-problem. While there are examples of stably free nonfree modules for many infinite groups G , there are few actual examples for finite groups. This paper offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…For finite groups, presentations with distinct second homotopy but the same deficiency were found by Metzler for C 5 3 [25, 16, p.105]. The case of quaternion groups has been the subject of much analysis [14,15,3,4], largely because of its relation to Wall's D(2)-problem. In 1965 Wall showed that for n > 2, if a finite cell complex is cohomologically n dimensional (in the sense of having no non-trivial cohomology in dimensions above n with respect to any coefficient bundle), then it is in fact homotopy equivalent to an actual n dimensional cell complex [31].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…For finite groups, presentations with distinct second homotopy but the same deficiency were found by Metzler for C 5 3 [25, 16, p.105]. The case of quaternion groups has been the subject of much analysis [14,15,3,4], largely because of its relation to Wall's D(2)-problem. In 1965 Wall showed that for n > 2, if a finite cell complex is cohomologically n dimensional (in the sense of having no non-trivial cohomology in dimensions above n with respect to any coefficient bundle), then it is in fact homotopy equivalent to an actual n dimensional cell complex [31].…”
Section: Introductionmentioning
confidence: 82%
“…Since the work of Johnson [14,15] and Beyl and Waller [3,4] in the early 2000's, the hunt has been on to find out if a finite balanced presentation of a quaternion group Q 4n can have non-standard second homotopy group. This has largely been fueled by the connection to Wall's famous D(2)-problem [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where (1) follows from the definition of the action of AutpGq using ψ : AutpGq Ñ pZ{|G|q ˆ, and (2) follows from Theorem A.…”
Section: Introductionmentioning
confidence: 99%